ENHANCE OF RELIABILITY OF LAND SAFETY FROM FIRE BASED ON COMPUTER VISION IN IMAGE PROCESSING - Khoirunsyah Dalimunthe; Muhammad Sayid Amir Ali Lubis; Rika Rosnelly; Wanayumini (INFOKUM, 2022)
Monitoring inland fires can help Human vision do amazing things, such as recognizing people or objects and navigating through obstacles, which can also be done using satellite imagery or cameras with image processing methods using uncrewed aircraft (UAV). Image processing is an activity where computers require a sensor that functions like the human eye and a computer program that acts as a data processor from the sensor. This research will focus on designing and implementing the computer vision metro de thresholding method, which is used for camera image data processing to detect fire inland fires. This value will be used as color filtering for parameters to detect fire objects and also as a threshold value for segmentation image.